Exploring Learners' Diversity in English Language Classrooms (Butwal Campus Journal, 2023)
This study aimed at exploring the diversity of students in English language classes. The technique of customizing classes to each student's unique interests, needs, and strengths is known as differentiated instruction (DI). It is a student-centered strategy that raises learners' engagement levels while addressing concerns of diversity with multiple teaching approaches and techniques. I adopted the social constructivism theory and interpretive inquiry as a research method to examine the diversity of learners. To achieve the purpose of the study, four research participants, two teachers and two students were selected from a public school in Rupandehi. I used a series of observations and unstructured interviews to gather the data from the participants. The diversity of the students was examined in terms of their performance, personality, and gender-based discrimination in class. This study explored that the teachers employed differentiated instruction to some extent in the English classroom by creating context, using group work, pair work, etc. However, they often ignored slow, shy and weak learners and frequently designed classroom activities for talented and extroverted learners. The study can contribute to English language teachers with insightful ideas to address and apply learners' diversities through differentiated instruction in classrooms.